Fennia.
Vol. 17 comprises "Atlas de Finlande, 1899," 1 v. text, and atlas; v. 30 comprises "Atlas de Finlande, 1910" 2 v. text, and atlas; v. 48 comprises "Atlas de Finlande," 1 v. text, and atlas. For record of other editions of the atlases and text see Suomen Maantieteellinen Seura (Founded 1888). Atlas de Finlande.